Peran Aktif Masyarakat Hukum Adat Dalam Pembangunan Ekonomi - Jenni Kristiana Matuankotta (SASI, 2018)
The active role of the customary law community in the process of economic development is very large supported by abundant natural wealth spread across the archipelago. This considerable potential will be better and can be supported by reliable human resources. Customary law communities can be included to participate in economic development. Empowerment of indigenous peoples with their local knowledge through economic development based on local wisdom can provide support, use and management of natural resources while maintaining the strength of their customary law, their spiritual abilities and the beliefs they embrace.